The regulatory role of the juxtamembrane region in the activity of the epidermal growth factor receptor - Boran, Aislyn D W (Biochemical Society transactions, 2012)
Although the EGFR (epidermal growth factor receptor) was discovered over 30 years ago, its mechanism of activation is still the subject of intense study. There are many published studies on the mechanism of EGFR activation and regulation, including biochemical and biophysical analyses and crystallographic structures of EGFR in different activation states and conformations, mutated at various amino acids or bound to different pharmacological inhibitors. The cumulative biochemical, biophysical and structural data have led to a nearly complete account of the mechanism of activation of EGFR. The role of the JXM (juxtamembrane) domain in EGFR structure and activity has only recently begun to be elucidated through biochemical, biophysical and structural studies. In the present article, I review the studies that have highlighted the role of the JXM domain in EGFR activation.